1984
DOI: 10.1038/jcbfm.1984.10
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Flow and Neurologic Outcome When Nimodipine is Given after Complete Cerebral Ischemia in the Dog

Abstract: Ten minutes of complete cerebral ischemia was produced in 26 dogs by temporary ligation of the aorta and the venae cavae. Twenty dogs received nimodipine, a calcium entry blocker, 10 micrograms kg-1 i.v. 2 min after the ischemic period, followed by 1 microgram kg-1 min-1 for 2-3 h. Six dogs received only the solvent used for nimodipine. Fourteen dogs received nimodipine for 3 h and were subsequently evaluated neurologically up to 48 h postischemia. In the 12 other dogs, CBF and metabolism were followed for 2 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
25
0
3

Year Published

1984
1984
1993
1993

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(30 citation statements)
references
References 16 publications
2
25
0
3
Order By: Relevance
“…" 16 A consistent finding in previous experiments and in ours has been that treatment with nimodipine improves survival after ischemic cerebral damage. In order to understand how nimodipine may benefit the gerbils with predicted 100% mortality, we should know the pathophysiological cause of death.…”
supporting
confidence: 75%
“…" 16 A consistent finding in previous experiments and in ours has been that treatment with nimodipine improves survival after ischemic cerebral damage. In order to understand how nimodipine may benefit the gerbils with predicted 100% mortality, we should know the pathophysiological cause of death.…”
supporting
confidence: 75%
“…9 Since the only measured variable that was improved by nimodipine was CBF, it was concluded that the post-ischemic hypoperfusion state does appear to contribute to the ultimate neurologic damage. In an identical study except that nimodipine was given only after the ischemic event, CBF was again higher during the hypoperfusion period in the nimodipine group 10 (CBF = 51 miyiOOg-'/min-', 34% of pre-ischemic control) than the untreated group. 4 However, in the neurologic function studies, when nimodipine was given only after ischemia, 10 neurologic outcome was intermediate and not significantly different from either the untreated group 14 or the pre-treated nimodipine group.'…”
Section: Discussionmentioning
confidence: 96%
“…In an identical study except that nimodipine was given only after the ischemic event, CBF was again higher during the hypoperfusion period in the nimodipine group 10 (CBF = 51 miyiOOg-'/min-', 34% of pre-ischemic control) than the untreated group. 4 However, in the neurologic function studies, when nimodipine was given only after ischemia, 10 neurologic outcome was intermediate and not significantly different from either the untreated group 14 or the pre-treated nimodipine group.' Flunarizine has been reported to be a potent inhibitor of calcium-induced constriction of isolated arteries, 24 being most effective in cerebral arteries.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, selective antagonists of excitatory amino acid receptors-in particular, N-methyl-D-aspartate (NMDA) antagonists-have not been effective in protecting the vulnerable CAl neurons in the four-vessel occlusion model of transient forebrain ischemia in rats (5-7). Similarly, classical calcium channel antagonists such as the dihydropyridines, which block L-type calcium channels, have also failed to protect neurons from the consequences of ischemia when administered after the ischemic episode (8,9). To develop therapies for preventing the brain damage caused by ischemia, we have investigated the utility of selectively blocking N-type calcium channels.…”
mentioning
confidence: 99%